Determinants of Customer Loyalty at Bank Syariah Indonesia KCP Medan Iskandar Muda 1 in Medan City - Nikmir Rohmiati; Arlina Nurbaiti Lubis; Beby Karina Fawzeea Sembiring (Universitas 17 Agustus 1945 Semarang, 2023)
This research aims to determine the effect of service quality and customer satisfaction on customer loyalty and also aims to increase customer loyalty. This research used customers of Bank Syariah Indonesia KCP Medan Iskandar Muda 1 in Medan City as respondents in filling out the questionnaire as many as 170 customers. The tests used in this research are data quality tests, classical assumption tests, influence tests and hypothesis tests. From the results of this research, it was found that the influence of service quality on customer loyalty is a significant influence where the significance value is 0.001 < 0.05 and tcount is greater than ttable (3.245 > 1.653), the influence of customer satisfaction on customer loyalty also has a significant influence where the significance value is 0.000 < 0.05 and tcount is greater than the table (3.742 > 1.653) and simultaneously service quality and customer satisfaction have a significant effect on customer loyalty where the significance value is 0.000 < 0.05 and fcount is greater than ftable (23.982 > 3.05). Meanwhile, the R2 value of 22.3% of this research is influenced by service quality and customer satisfaction variables, while the remaining 77.7% is influenced by service quality and customer satisfaction variables. influenced by other variables not examined in this study.